Influence of Rice Husk Ash on Characteristics of Earth Cement Blocks - Seevaratnam, V.; Dilukshan, U.; Sathiparan, N. (Cambridge University Press, 2020)
This paper presents an experimental study on the characteristics of earth cement blocks with Rice Husk Ash (RHA) as a partial replacement to cement. The replacement of RHA content is limited to 0%, 5%, 10%, 15% and 20% by mass of the total binder in the earth cement block. The experiments on earth cement blocks investigate the compressive strength and flexural tensile strength for mechanical properties and water absorption, sorption rate and erosion against water spray for its durability. Due to the high content of SiO2 in RHA with great reactivity, a significant increase in the compressive and flexural tensile strength of earth cement blocks was observed up to 10% RHA content. However, the durability of earth cement blocks becomes adverse with the increasing percentage of RHA replacement, but within the allowable limit. The experimental results indicate that to some extent, RHA based earth cement blocks have a significant potential for reduction in cement used in the construction industry.